Acetylcholine contributes to control the physiological inflammatory response during the peri-implantation period - Paparini, Daniel Esteban (2015)
Maternal antigen-presenting cells attracted to the pregnant uterus interact with trophoblast cells and modulate their functional profile to favour immunosuppressant responses. Non-neuronal cholinergic system is expressed in human cytotrophoblast cells and in immune cells with homeostatic regulatory functions. The aim of this work was to evaluate whether non-neuronal acetylcholine conditions maternal monocyte and DC migration and activation profiles.